التوغل البريطاني منذ القرن١٨-١٩ في جنوب كوردستان تمهيدا لاحتلاله - برزنجي, كمال طاهر رشيد (Sulaimani Journal for Humanities, 2021)
Kurdistan is a country that destiny did not want freedom and independence to be written in the era of the emergence of nation-states, not because its inhabitants overlooked this aspect which the people yearn for throughout the globe, but they took all possible means to preserve identity and freedom of life and not submit to restriction, persecution and enslavement, but a strategy Its location as a country rich with all the human needs of wealth above and below, in addition to the beauty of its attractive nature and its sanctity, which the prophets called for with its blessing because it is considered the cradle of the second humanity and the sanctuary of the prophets and their shrines. These reasons made Kurdistan the goal of the ambitions of invaders and greedy people throughout history, and its history record is full of Muslim facts, Finally, the British ambitions and attempts to penetrate them in the countries of Kurdistan since the nineteenth century began, and they began implementing their plans in various ways to military intervention and direct occupation, and the conflict was a dispute between the lacking and self-reliant Kurds and the boasted English and the help of all the number added to his mercenaries and the equipment and treasures of his huge colonies. Britain embarked on methods of delusion and deception with the Kurdish leaders led by Sheikh Mahmoud Al-Barzanji to get the goal to stabilize the foot, and he is the one who used the English by inviting them to stave off the dangers of war on Kurdistan, but they turned against him and removed him in the end and did not fulfill their promises they made to him after achieving their goals. Our research deals with the content of the events and their developments in that era with realistic analyzes of their events. The documents and basic sources of the subject browsed and reached facts that were relatively vague and tried to uncover the mystery and raise the curtain inferred from it. It consists of discussions and demands with the conclusion and some recommendations, so we hope that our research will be accepted without Adoration and there is no perfection except God, and providing us with what enriches the research, and we ask God to help us and you in achieve the scientific goals in a way that serves generations and countries.